POKRYWA ŚNIEŻNA W ZACHODNIEJ CZĘŚCI BESKIDÓW ZACHODNICH - DYSZY, WIKTORIA; SZYGA-PLUTA, KATARZYNA (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2020)
The work presents the occurrence of snow cover in the western part of the Western Beskids in the years 1991–2020. We have analysed data from climate research stations of the IMGW-PIB located in Brenna, Laliki, Zawoja, Radziechowy (1991–2007)/Nowy Dwór (2008–2020). We calculated the number of days with snow cover for each winter seasons, the number of days with permanent snow cover, the potential duration of snow cover and the sum of seasonal snow cover thicknesses. The snowiness classes of Chrzanowski winters and the snowiness index of Paczos were determined from the sums of the thickness of the snow cover. The snowiest season was the 2005/06 winter season, while the thinnest snow cover was observed in the 2013/14 season. There are clear relationships between the height above sea level and the time of snow cover occurrence, as well as its thickness.